POTENTIALLY LOW-CQST DRINKING WATER"DEFLUORIDATION METHODS - A REVIEW - Woldeyes, Belay; Dendena, Lemma; Terera, Nurelegne (Zede Journal of Ethiopian Engineers and Architects, 2023)
£xcu.Jlve fluoride in drinpng water caUJtJ dental and skeletal health problems commo,uy broom D.t jluorrui . Both high fluoride concentration and jluori.fill are prtvafent in many parts ’ of the Ethiopian rift valley. The recommended limit of fluoride by the World Health Organization (WHO) rongl!J from 0.5 - I,J ppm, whereOJ water with jluorid concentratioru OJ high OJ 9 mg/J are uJed in .famt parI of the Ethiopian RifI’Yalley. A number of stllillts have been conducted to Identify the fluoride roncentratiOfU in diffirent oreeu and their effect on the population. However only limited research haw been CQ"ied out to develop appropriate deft/Wridation techniques offordable for dewloping countries lilu Ethiopia.